Impacts of social networks on linguistic practices: (re) thinking activities to teach courtesy strategies in the Spanish language - Gregolin, Isadora Valencise [UNESP] (Univ Sao Paulo, Fac Filosofia, 2017)
The article discusses the impact of digital networks in the ways young people socialize today and reflects on the teaching of courtesy strategies (Escandell-Vidal, 1995; Alvarez Muro, 2005) in Spanish language, considering some activities developed by preservice teachers during their supervised practice. The initial results suggest that these activities bring the students into a closer contact with the foreign language and contribute to increase their cultural repertoire and to develop an intercultural vision without stereotypes.
Keywords: Spanish; courtesy; social network